The Making of the Meadowlands: How Ancaster's Fields Became Hamilton's Suburbs - Parsons, Jeremy (My University, 2015)
In an age of increasing urbanization, rural communities and agricultural lifestyles are quickly disappearing. Many local, pastoral histories have been buried under the new narratives of modern suburban development. Do such places, located along the rural-urban fringe, contain accounts worth memorializing? This thesis is a case study of the Ancaster Meadowlands—a growing neighbourhood within the City of Hamilton, Ontario. It explores the process of suburban growth and uncovers the local history of a landscape. As a narrative, the study traces land-use change over time, displaying the area’s evolution from a site of Neolithic settlement, to an important Loyalist village, and finally to a large suburban neighbourhood with commercial and residential components. Three principal methods are employed: resident interviewing, key informant interviewing, and archival research. Themes elicited in this study include land-use conflict, NIMBYism, real-estate volatility, and the interconnectedness of politicians and developers. Given that there are few case studies of contemporary suburban development, this study provides a rare illustration of the multi-faceted process of expansion around a Canadian city while also supplying a historical account of local importance.
Keywords: Urban planning; land development; suburbs; suburban; NIMBY; Ancaster; Hamilton; case study; land-use conflict; wetlands